Association of Hyperferritinemia With Distinct Host Response Aberrations in Patients With Community-Acquired Pneumonia. (31st January 2022) - Brands, Xanthe; van Engelen, Tjitske S R; de Vries, Floris M C; Haak, Bastiaan W; Klarenbeek, Augustijn M; Kanglie, Maadrika M N P; van den Berk, Inge A H; Schuurman, Alex R; Peters-Sengers, Hessel; Otto, Natasja A; Faber, Daniël R; Lutter, René; et al.
Abstract: Background: Strongly elevated ferritin levels have been proposed to reflect systemic hyperinflammation in patients admitted to the intensive care unit. Knowledge of the incidence and pathophysiological implications of hyperferritinemia in patients with acute infection admitted to a non–intensive care setting is limited. Methods: We determined the association between hyperferritinemia, defined by 2 cutoff values (500 and 250 ng/mL), and aberrations in key host response mechanisms among patients with community-acquired pneumonia (CAP) on admission to a general hospital ward (clinicaltrials.gov NCT02928367; trialregister.nl NTR6163). Results: Plasma ferritin levels were higher in patients with CAP (n = 174; median [interquartile ranges], 259.5 [123.1–518.3] ng/mL) than in age- and sex-matched controls without infection (n = 50; 102.8 [53.5–185.7] ng/mL); P  < .001); they were ≥500 ng/mL in 46 patients (26%) and ≥250 ng/mL in 90 (52%). Measurements of 26 biomarkers reflective of distinct pathophysiological domains showed that hyperferritinemia was associated with enhanced systemic inflammation, neutrophil activation, cytokine release, endothelial cell activation and dysfunction, and activation of the coagulation system. Results were robust across different cutoff values. Conclusions: Hyperferritinemia identifies patients with CAP with a broad deregulation of various host response mechanisms implicated in the pathogenesis of sepsis. This could inform future therapeutic strategies targeting subgroups within the CAP population. Abstract : Extremely elevated plasma ferritin levels have been linked to exaggerated systemic inflammation. Here we show that in patients hospitalized for community-acquired pneumonia, more moderate hyperferritinemia is associated with elevated levels of plasma biomarkers reflecting disturbances in key host response pathways.